Determinants of Bank Performance through Camel Ratio, Digitalization, and Bank Size - Kayani, Indah; Hakiman, Hakiman (Green Publisher Indonesia, 2023)
In general, this research aims to analyze the effect of CAMEL’s factors, namely BOPO, CAR, NPL, and LDR on the bank's financial performance. As well as the external factors of Digitalization and Bank Size on the bank's financial performance. In this case, the bank's financial performance is proxied by ROA. The population in this study are conventional banks registered with the Financial Services Authority totaling 107 banks. The sampling technique used purposive sampling with a total sample of 10 banks that met the criteria. The approach used is panel data regression with a random effect model as the best model. Data analysis software uses E-Views 12. The results of this study found that BOPO and CAR have a negative effect on financial performance. LDR, Digitization, and Bank Size each have a positive effect on financial performance. But, NPL does not affect bank performance. From these results, banks are expected to be able to improve financial performance and bank management performance so that creditors have a good perception of bank performance in the future. And must be able to maintain the soundness of the bank by considering all possible risks that will arise. In research, bank digitization has shown quite good results. However, banks must continue to innovate on digital banking while continuing to be accompanied by an increase in the number of customers and pay attention to the infrastructure costs of digitalization.